Demand-oriented differentiated multi-zone thermal environment: Regulating air supply direction and velocity under stratum ventilation. (1st July 2022) - Liu, Yemin; Liu, Yang; Shao, Xiaoliang; Liu, Yu; Huang, Chun-E; Jian, Yiwen
Abstract: Different thermal preferences from occupants in a shared space must be satisfied simultaneously. For a ventilated room with multiple air supply inlets, differentiated thermal environment parameters can be maintained in different subzones by liberating the unified air supply parameter adjustment from all the air supply inlets and subsequently adopting independent adjustment of different groups of air supply inlets near different subzones. In this study, the achievable difference level of thermal environment was investigated numerically based on the stratum ventilation. Primarily, the effect of independently regulating the air supply directions and velocities from two inlet groups on the difference in the local thermal environment between subzones was analyzed. The position of occupants and heat distribution were considered as the influencing factors. Further, the predicted mean vote (PMV) index was utilized to evaluate the cool or warm degree of the local thermal environment while the draught rate (DR) and percentage dissatisfied (PD) indices were utilized to evaluate the local thermal discomfort. The results obtained indicated that regulating air supply direction significantly affected the differentiated thermal environment, with the achievable ΔPMV between subzones up to 1.46. Moreover, the increase in air supply velocity based on the appropriate air supply direction further expanded the ΔPMV. In addition, the change in heat source position resulted in a ΔPMV decrease of 0.36. No strong draught risk and local thermal discomfort caused by the vertical temperature difference were observed. This study is expected to provide guidance for the maintenance of demand-oriented zoning thermal environment. Highlights: Differentiated thermal environments in multi-occupied subzones were investigated. Differential potential was revealed by adjusting air supply directions and velocities. Regulating air supply direction maintains ΔPMV between occupied subzones up to 1.46 Regulating air supply velocity based on appropriate air supply direction expands ΔPMV. No draught risk and local thermal discomfort are found during zonal ventilation.